Strategies to Promote Healthy Eating Among University Students: A Qualitative Study Using the Nominal Group Technique - Wongprawmas, Rungsaran; Sogari, Giovanni; Menozzi, Davide; Mora, Cristina (Frontiers in Nutrition, 2022)
Introduction The years spent at university are critical in terms of altering people's dietary patterns. This study aimed to: (1) understand the main dietary changes that students experience after starting university; (2) determine the personal and objective factors that hinder healthy eating, and (3) define possible strategies to facilitate healthier diets among university students. Methods The nominal group technique (NGT) was used to elicit ideas from 39 students from the University of Parma, Italy. The sample comprised 16 freshmen and 23 non-freshmen. Participants prioritized and weighed their top five ideas regarding dietary changes, barriers to healthy eating, and possible strategies to maintain a healthy diet. A thematic analysis was conducted to compare the priorities across groups. Results Forty-three themes were elected as the most significant changes related to diet, 39 themes related to personal barriers, 43 themes related to objective barriers, and 55 themes related to strategies. A lack of time for cooking, low financial availability, consumption of unvaried food or junk food, and gaining knowledge about food were identified as the main changes. Personal barriers to eating healthy were intrinsic (i.e., lack of willpower, personal gluttony, and little effort in cooking preparation), poor dietary information, and a busy lifestyle. Market and financial factors (i.e., the high price of healthy products and low financial availability), as well as social factors (i.e., the negative influence of social networks, childhood food education, and origin/tradition), emerged as objective barriers. Possible strategies that could encourage students to adopt a healthy diet include varying the food products offered in university canteens, including organizing spaces where students who prepare meals from home can warm up and eat their food. Student discounts at supermarkets and information on nutrition and a healthy diet were also identified as important ways of supporting students. Conclusion and Implication for Practice In order to make students part of the solution, the NGT provided them with the opportunity to equally contribute their ideas and opinions about having a healthy diet in a university context. This could potentially lead to tailor-made solutions for policymakers, educators, and foodservice providers in promoting healthy eating habits.